2019
DOI: 10.21608/adjalexu.2019.57362
|View full text |Cite
|
Sign up to set email alerts
|

Blood Vessel Density as a Predictor in Oral Squamous Cell Carcinoma Using Cd34

Abstract: INTRODUCTION:Oral squamous cell carcinoma (OSCC) accounts for more than 90% of all oral cancers. Despite advances in the approach to locally advanced disease, about 50% of the tumors will recur. Fifty percent of patients present nodal involvement that is detectable during diagnosis. Of this group, less than 40% survive after five years, compared with a 90% survival rate for patients without metastasis. If the lesion is detected at an early stage and treated effectively, the survival rate could exceed 50%. Many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Our findings are consistent with those of Sappayatosok et al 17 However, Elmorsy et al found a significant correlation between MVD and nodal stage (p<0.001). 25 Few studies have correlated MVD with VEGF. In our study, we did not find a significant correlation between VEGF and MVD (p=0.593).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with those of Sappayatosok et al 17 However, Elmorsy et al found a significant correlation between MVD and nodal stage (p<0.001). 25 Few studies have correlated MVD with VEGF. In our study, we did not find a significant correlation between VEGF and MVD (p=0.593).…”
Section: Discussionmentioning
confidence: 99%